Identifying control structure of multi-joint coordination in dart throwing: the effect of distance constraint - S.H. HosseiniZarch; S. Arsham; S.F. Tabatabaei Ghomshe; M.H. Honarvar (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Background: This study used the uncontrolled manifold (UCM) approach to study joint coordination underlying the control of task-related variables important for success at dart throwing skill. Success at a task can be achieved, in principle, by always adopting a particular joint combination. In contrast, we adopt a more selective control strategy: variations of the joint configuration that leave the values of essential task variables unchanged are predicted to be less controlled (i.e., stabilized to a lesser degree) than joint configuration changes that shift the values of the task variables. Objectives: How this abundance of motor solutions is managed by the nervous system and whether and how the throwing in different distances affects the solution to joint coordination was investigated in this study. Methods: Our experimental task involved dart throwing to a target under three conditions (standard, short and long distance) that it performed by fifteen dart professional and semiprofessional athletes. The four joint angles of the arm were obtained from the recorded positions of markers on the limb segments. The variability of joint configurations was decomposed into components lying parallel to those sets and components lying in their complement with respect to control of the path of the arm's center of mass and spatial position of the hand. Results: When performing the task in all three different conditions, fluctuations of joint configuration that affected arm's center of mass and spatial position variables were much reduced compared with fluctuations that did not affect these variables. The UCM principle applied to arm's center of mass and spatial position thus captures the structure of the motor control system across different parts of joint configuration space as the movement evolves in time. Moreover, constraints representing an invariant arm's center of mass or the spatial position structured joint configuration variability in the early and mid-portion of the movement trajectory, but not at the time of throwing. This specific control strategy indicate a target can be hit successfully also by controlling irrelevant directions in joint space equally to relevant ones. Conclusion: The results suggests a specific control strategy in which changes of joint configuration that are irrelevant to success at the task are selectively released from control. As a result, the method can be successfully used to determine the structure of coordination in joint space that underlies the control of the essential variables for a given task.